A comprehensive overview on water-based energy storage systems for solar applications. (November 2022) - Danehkar, Shaghayegh; Yousefi, Hossein
Abstract: The development of proper storage medium for renewable sources with high intermittency (such as solar or wind) is an essential steps towards the growth of green energy development and enabling them to compete with fossil fuel resources in the current market. While the emerging of new generation of storage mediums, such as lithium based batteries is revolutionizing the world of renewable energy storage systems, many counties are still far behind in the growing market of storage technologies due to budget-related issues and hindering policies. In other world for many countries investment on new technologies which are still under the experimental stage of marketing, is too risky. It is more efficient for such countries to focus on well-developed and reliable storing technologies. This is the main reason why fossil fuel systems still thriving significantly in this field. Under these circumstances relying on "water-based" storage systems to compete with fossil fuels dominancy is an efficient solution due to various advantages of water-based systems including high specific heat, non-toxicity, lower costs, chemical stability, availability and high capacity rate during charge and discharge. While liquid water storage are highly suitable for operating temperature of 20–80 °C, using the steam accumulation form of such medium is easily suitable for high temperature applications such as power generation or other industrial applications. Aside from thermal applications of water-based storages, such systems can also take advantage of its mechanical energy in the form of pumped storage systems which are vastly use for bulk energy storage applications and can be used both as integrated with power grid or standalone and remote communities. The main goal of this study is to comprehensively explore the exciting water-based storage systems (including ice and steam) in terms of technical advances, economic growth and environmental challenges which have been significantly overlooked in the previous similar studies. Highlights: Solar systems coupled with water-based storage have a great potential to alleviate the energy demand. Solar systems linked with pumped hydro storage stations demonstrate the highest potential efficiency up to 70% to 80%. Many form of these systems takes of too much space compared to battery-based storage technologies.